Gestión administrativa de la compañia de transporte chilincargasa s.a del recinto mata de cacao - Sambrano García, Salomon Alexander (2022)
The present realization of the case study should be stated that it is of vital importance since it will be possible to identify the importance of the administrative management of the transport company CHILINCARGASA SA of the Mata de Cacao site, whose general objective is to analyze how the administrative processes intervene within the transport company chilincargasa SA Since in the problem carried out, the lack of planning in the company Chilincargasa SA has resulted in the disorder of the departures of the vehicles at the established times, since at the time of the tours they usually go ahead in shifts and this causes anger. Among the drivers, also due to the lack of personnel within the administrative area of the company, this causes little planning for all the processes that the company carries out in the work area, causing discomfort among its workers. In a referential way, the application of a survey was carried out in which various factors are identified, such as, for example, it is determined that vehicle maintenance costs are expenses that cannot be avoided because it is one of the requirements to obtain the operating permit. that it is mandatory to carry out controls on vehicles and therefore these expenses are not made every day, but twice a year and it is not considered a detrimental expense for the company to be able to say that it is losing profits by carrying out this type of maintenance on their vehicles. Therefore, carrying out a full administration in the company is of vital importance for the company.